An open, observational clinical study of neoadjuvant therapy in resectable stage III non-small cell lung cancer - Qi, Yuwen; Gu, Linping; Shen, Jie; Yao, Yaxian; Zhao, Yi; Lu, Shun; Chen, Zhiwei (Frontiers in Oncology, 2023)
Background: This open, observational clinical study aimed to investigate the efficacy, safety and survival outcomes of neoadjuvant chemotherapy, neoadjuvant immunotherapy with(out) chemotherapy and neoadjuvant targeted therapy among resectable stage III non-small cell lung cancer (NSCLC) patients (NCT04197076) in real world. 48 of the 57 evaluable patients were included in this interim analysis. Methods: This study was conducted at Shanghai Chest Hospital and included eligible NSCLC patients who were 18 years or older and had resectable clinical stage III disease. Surgical resection was conducted after neoadjuvant chemotherapy (13 patients), immunotherapy with(out) chemotherapy (26 patients), and targeted therapy (9 patients). Disease-free survival (DFS) was evaluated as the primary endpoint. The secondary endpoint was pathological complete response (pCR) rate. Clinical response rate (cRR), related adverse events (AEs), surgical feasibility and pathological features were also discussed in this study. Results: Significant differences in DFS were noted between chemotherapy and immunotherapy [7.7 months (range, 3.1 to 23.2 months) vs. 9.6 months (range, 4.0 to 47.9 months); P=0.032], and between chemotherapy and targeted therapy [7.7 months (range, 3.1 to 23.2 months) vs. 13.2 months (range, 7.5 to 32.2 months); P=0.015], but not between immunotherapy and targeted therapy (P=0.500). Subgroup analysis also favored neoadjuvant immunotherapy and targeted therapy. 5 patients achieved pathological complete response (pCR), all of whom were in the neoadjuvant immunotherapy arm, leading to a pCR rate of 19.2% in this arm. Treatment-emergent adverse events (TEAEs) of over grade 3 occurred in 11 patients (19.3%), with 5 (29.4%) in the chemotherapy arm, 5 (16.7%) in the immunotherapy arm and 1 (10.0%) in the targeted therapy arm. One grade 4 and one grade 2 surgery-related serious adverse event occurred in the neoadjuvant chemotherapy and immunotherapy arm, respectively. Conclusion: In patients diagnosed with resectable stage III NSCLC, neoadjuvant immunotherapy and neoadjuvant targeted therapy were associated with significantly longer disease-free survival compared with neoadjuvant chemotherapy. Clinical and pathological response rates were also higher in the immunotherapy and targeted therapy arm. Adverse events were found to be manageable and similar across all three groups, and surgical feasibility favored immunotherapy or targeted therapy rather than chemotherapy. Clinical Trial Registration: https://clinicaltrials.gov/ct2/show/NCT04197076?recrs=a&cond=NCT04197076&draw=2&rank=1.